Localized Delivery of Amifostine Enhances Salivary Gland Radioprotection - Varghese, J J; Schmale, I L; Mickelsen, D; Hansen, M E; Newlands, S D; Benoit, D S W; Korshunov, V A; Ovitt, C E (Journal of dental research, 2018)
Radiotherapy for head and neck cancers commonly causes damage to salivary gland tissue, resulting in xerostomia (dry mouth) and numerous adverse medical and quality-of-life issues. Amifostine is the only Food and Drug Administration-approved radioprotective drug used clinically to prevent xerostomia. However, systemic administration of amifostine is limited by severe side effects, including rapid decrease in blood pressure (hypotension), nausea, and a narrow therapeutic window. In this study, we demonstrate that retroductal delivery of amifostine and its active metabolite, WR-1065, to murine submandibular glands prior to a single radiation dose of 15 Gy maintained gland function and significantly increased acinar cell survival. Furthermore, in vivo stimulated saliva secretion was maintained in retrograde-treated groups at levels significantly higher than irradiated-only and systemically treated groups. In contrast to intravenous injections, retroductal delivery of WR-1065 or amifostine significantly attenuated hypotension. We conclude that localized delivery to salivary glands markedly improves radioprotection at the cellular level, as well as mitigates the adverse side effects associated with systemic administration. These results support the further development of a localized delivery system that would be compatible with the fractionated dose regimen used clinically.